1998
DOI: 10.1097/00004836-199800001-00022
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Changes in the Glandular Stomach and Duodenum in an H. pylori-infected Mongolian Gerbil Model

Abstract: We have established a Helicobacter pylori-infected Mongolian gerbil model following Hirayama's method to investigate gastric diseases associated with H. pylori infection. We orally administered the culture broth of H. pylori ATCC 43504 to 8-week-old male Mongolian gerbils. After this, the gerbils were fed in a vinyl isolator. Subsequently, over the course of 48 weeks some of them were sacrificed for histopathologic examination and H. pylori culture. H. pylori colonization in the glandular stomach was seen in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The animals were subjected to water-immersion 12 weeks after H. pylori infection, when chronic gastritis, but not ulcers, was known to be present. 16 According to the method of Takagi and Okabe, 17 each animal was restrained and immersed in water at 21°C in an upright position, up to its xiphoid process, for 30, 120, or 720 min. Immediately after the immersion, the stomach was removed, and an incision was made along the greater curvature.…”
Section: Experimental Schedulementioning
confidence: 99%
“…The animals were subjected to water-immersion 12 weeks after H. pylori infection, when chronic gastritis, but not ulcers, was known to be present. 16 According to the method of Takagi and Okabe, 17 each animal was restrained and immersed in water at 21°C in an upright position, up to its xiphoid process, for 30, 120, or 720 min. Immediately after the immersion, the stomach was removed, and an incision was made along the greater curvature.…”
Section: Experimental Schedulementioning
confidence: 99%
“…Sawada et al revealed that acute inflammation, immature epithelium, and erosions were observed already 2 weeks after H. pylori infection, whereas chronic inflammation was noticed 4 weeks upon H. pylori infection. In addition, they found that gastric ulcers and intestinal metaplasia develop from 12 to 24 weeks, respectively [9].…”
mentioning
confidence: 99%
“…Since Hirayama et al (10) reported the establishment of persistent H. pylori infection in Mongolian gerbils as an animal model in 1996, many investigations on the association between H. pylori and gastric diseases have been carried out (12,17,21,29,30) and, recently, some reported that H. pylori was directly related to gastric carcinogenesis (9,11,32,40). The purposes of almost all of the studies which have ever been carried out were predominantly focused on the measurement of the amount of gastric colonization, the serum antibody titer against H. pylori, and histopathological observation of the stomach.…”
mentioning
confidence: 99%